Fashioning Jews Clothing, Culture and Commerce (SJC #24) - Greenspoon, Leonard J. (Purdue University Press, 2013)
This volume presents papers delivered at the 24th Annual Klutznick Harris Symposium, held at Creighton University in October 2011. The contributors look at all aspects of the intimate relationship between Jews and clothing, through case studies from ancient, medieval, recent, and contemporary history. Papers explore topics ranging from Jewish leadership in the textile industry, through the art of fashion in nineteenth-century Vienna, to the use of clothing as a badge of ethnic identity, in both secular and religious contexts. Contents: Shmattas in the North, Shmattas in the South: The Civil War and the Birth of the American Clothing Industry (Adam Mendelsohn); Weimar Jewish Chic from Wigs to Furs: Jewish Women and Fashion in 1920s Germany (Kerry Wallach); Jewish Photographers and the Body in the Weimar Republic (Nils Roemer); Female Tallitot: Creating American Jewish Women's Religious Experience through Fashion (Rachel Gordan); Clothes and the Weaving of American Jewish Comedy (Ted Merwin); The Jewish Badge in Renaissance Italy: The Iconic O, the Yellow Hat, and the Paradoxes of Distinctive Sign Legislation (Flora Cassen); How a Rabbi Should Be Dressed: The Question of Cassock and Clerical Clothing among Italian Rabbis from the Renaissance to Contemporary Times (Asher Salah); The "Disinherited" Priesthood: A Look into Biblical Israel's Unshod Priest (Christine Palmer); Costume and Identity in the Dura Europos Synagogue Paintings (Steven Fine); Picturing Vienna's New Woman: Madame d'Ora meets Ella Zwieback-Zirner (Lisa Silverman); Aboriginal Yarmulkes, Ambivalent Attire, and Ironies of Contemporary Jewish Identity (Eric Silverman); Fashioning Jews on the Screen: The Impact of Dress on Crafting the Jewish Image in Film and Television (Brian Amkraut)